2021
DOI: 10.1121/10.0004779
|View full text |Cite
|
Sign up to set email alerts
|

Speech intelligibility in a realistic virtual sound environment

Abstract: Employing realistic, yet controlled sound scenarios for the evaluation of hearing aid (HA) algorithms in a virtual sound environment (VSE) has the potential to improve HA users' real-world listening experience and performance. In the present study, so-called critical sound scenarios (CSS) were defined as acoustic scenes that HA users experience as important, difficult and common, and selected through ecological momentary assessment (EMA), inspired by results from recent studies. The scenarios were acquired in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 44 publications
2
11
0
Order By: Relevance
“…It was found that both unaided and aided SRTs were significantly increased inside both realistic VSEs compared to a reference condition employing quadraphonic SSN as a masker. This is consistent with previous studies, which showed increased spectral and modulation-spectral energetic masking for realistic noises as well as a detrimental effect of intelligible speech in the maskers on SI (Best et al, 2015;Mansour et al, 2019). Despite the acoustic differences, SI was similar between the two realistic noise types, suggesting that precise acoustic details in the reproduced environment may be less important than its overall loudness and number of interfering sources.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…It was found that both unaided and aided SRTs were significantly increased inside both realistic VSEs compared to a reference condition employing quadraphonic SSN as a masker. This is consistent with previous studies, which showed increased spectral and modulation-spectral energetic masking for realistic noises as well as a detrimental effect of intelligible speech in the maskers on SI (Best et al, 2015;Mansour et al, 2019). Despite the acoustic differences, SI was similar between the two realistic noise types, suggesting that precise acoustic details in the reproduced environment may be less important than its overall loudness and number of interfering sources.…”
Section: Discussionsupporting
confidence: 91%
“…The main aim of this study was to investigate the impact of applying in situ background-noise recordings as maskers in a speech intelligibility task conducted with and without hearing aids. Consistently with previous work (Best et al, 2015;Mansour et al, 2019), employing realistic noise maskers resulted in increased SRTs compared to artificial noise maskers. This reduction in SI in realistic backgrounds containing a mixture of interfering talkers has been linked to energetic speech-on-speech masking of the interferers on the target speech in the spectral and modulation-spectral domains (Brungart et al, 2006;Jørgensen and Dau, 2011) as well as informational masking caused by the intelligibility of the interferers (Westermann and Buchholz, 2015).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This means that by selecting the right environment a useful operating point (where scores are away from both ceiling and floor) can be found for listeners across a wide range of hearing abilities. Depending on the specific purpose, the test environment may be selected based on the individual’s hearing loss, their reported speech-in-noise problem, or the relevance of a test environment (e.g., see Mansour et al, 2021 ). Furthermore, we demonstrated that, within our framework, the choice of speech materials not only affected the realism of the stimuli but also changed the difficulty of the listening task.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we also recreated a virtual 3D acoustic environment to make the task more ecologically valid. Such virtual acoustic realities have been recently shown to increase the difficulty of the listening task compared to lab-based assessments due to the added complexity, especially in patients with HI [ 65 , 66 ]. In the presence of a virtual 3D acoustic environment, it is possible that the intelligibility decreased excessively in both high and low background noise, and that young children with CIs subsequently found the task of listening to speech too demanding when background noise was present.…”
Section: Discussionmentioning
confidence: 99%